On the Need for Mixed Media in Distributed Requirements Negotiations - Damian, D.; Lanubile, F.; Mallardo, T. (IEEE transactions on software engineering, 2008)
Achieving agreement with respect to software requirements is a collaborative process that traditionally relies on same-time, same-place interactions. As the trend toward geographically distributed software development continues, colocated meetings are becoming increasingly problematic. Our research investigates the impact of computer-mediated communication on the performance of distributed client/developer teams involved in the collaborative development of a requirements specification. Drawing on media-selection theories, we posit that a combination of lean and rich media is needed for an effective process of requirements negotiations when stakeholders are geographically dispersed. In this paper, we present an empirical study that investigates the performance of six educational global project teams involved in a negotiation process using both asynchronous text-based and synchronous videoconferencing-based communication modes. The findings indicate that requirement negotiations were more effective when the groups conducted asynchronous structured discussions of requirement issues prior to the synchronous negotiation meeting. Asynchronous discussions were useful in resolving issues related to uncertainty in requirements, thus allowing synchronous negotiations to focus more on removing ambiguities in the requirements.